Proteus endocarditis in an intravenous drug user. (26th November 2015) - Goel, Rohan; Sekar, Baskar; Payne, Mark N
Abstract : Infective endocarditis (IE) is a life-threatening condition with adverse consequences and increased mortality, despite improvements in treatment options. Diagnosed patients usually require a prolonged course of antibiotics, with up to 40–50% requiring surgery during initial hospital admission. We report a case of a 42-year-old intravenous drug user who presented feeling generally unwell, with lethargy, rigours, confusion and a painful swollen right leg. He was subsequently diagnosed with Proteus mirabilis endocarditis (fulfilling modified Duke criteria for possible IE) and deep vein thrombosis (DVT). He was successfully treated with single antibiotic therapy without needing surgical intervention or requiring anticoagulation for his DVT. Proteus endocarditis is extremely uncommon, with a limited number of case reports available in the literature. This case illustrates how blood cultures are invaluable in the diagnosis of IE, especially that due to unusual microorganisms. Our case also highlights how single antibiotic therapy can be effective in treating Proteus endocarditis.